2018
DOI: 10.1111/ijau.12113
|View full text |Cite
|
Sign up to set email alerts
|

Effective association between audit committees and the internal audit function and its impact on financial reporting quality: Empirical evidence from Omani listed firms

Abstract: The role of the audit committee in oversight of the internal control and internal audit function has grown in the last decades as corporate governance mechanisms after the dramatic scandals and failures. This paper examines the impact of the audit committee and the presence of internal audit function on a company's financial reporting quality. Moreover, this study focus on the association between the audit committee and internal audit function and company's financial reporting quality measured as accruals qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 63 publications
(141 reference statements)
2
46
0
7
Order By: Relevance
“…Based on social capital theory and resource-dependence theory, which argue that due to the business connections, AC members could gain valuable experience (including governance experience) from serving on other boards, which provides them with the skills and motivations to seek greater assurances in the area of FRQ (Sultana et al 2019). The results are in line with the agency and resource-dependence arguments as well as Yang and Krishnan (2005), Eulaiwi et al (2016), Gebrayel et al (2018 and Al Lawati and Hussainey (2020). Furthermore, Abdelbadie and Salama (2019), Trinh et al (2020a) and Elnahass et al (2020) provide evidence that interlocked directors are very beneficial to companies in terms of the extended knowledge, wider channel networks and broader experience that these members gain from serving on different companies.…”
Section: Ac Multiple Directorshipmentioning
confidence: 52%
See 3 more Smart Citations
“…Based on social capital theory and resource-dependence theory, which argue that due to the business connections, AC members could gain valuable experience (including governance experience) from serving on other boards, which provides them with the skills and motivations to seek greater assurances in the area of FRQ (Sultana et al 2019). The results are in line with the agency and resource-dependence arguments as well as Yang and Krishnan (2005), Eulaiwi et al (2016), Gebrayel et al (2018 and Al Lawati and Hussainey (2020). Furthermore, Abdelbadie and Salama (2019), Trinh et al (2020a) and Elnahass et al (2020) provide evidence that interlocked directors are very beneficial to companies in terms of the extended knowledge, wider channel networks and broader experience that these members gain from serving on different companies.…”
Section: Ac Multiple Directorshipmentioning
confidence: 52%
“…Extant evidence on the association between AC meetings and monitoring effectiveness is mixed. On the one hand, based on agency perspective, some studies find that the number of AC meetings is associated with higher FRQ (proxied by different measures, such as auditor selection and auditor quality, fewer restatements and less aggressive earnings management) (Abbott and Parker 2000;Xie et al 2003;Abbott et al 2004;Bédard et al 2004;Gebrayel et al, 2018). In line with this, a positive relationship is found between AC meeting frequency and the voluntary disclosure level (Li et al 2012;Allegrini and Greco 2013;Haji 2015;Al-Maghzom et al 2016;Buallay and Al-Ajmi 2019;Raimo et al 2020).…”
Section: Ac Meeting and Fldmentioning
confidence: 86%
See 2 more Smart Citations
“…This study found a big positive relationship between internal audits and effective company governance. Gebrayel, Jarrar, Salloum, and Lefebvre, (2018) examined the impact of the audit committee and also the presence of internal audit operate on a company's money coverage quality. They mentioned that the inner audit operation is taken into account as a crucial company governance mechanism to safeguard the standard of economic coverage.…”
Section: Critical Review Of the Literaturementioning
confidence: 99%